Larvae of Huxelhydrus syntheticus Sharp, 1882 (Coleoptera: Dytiscidae: Bidessini) - Michat, Mariano C.; Alarie, Yves; Hájek, Jiří (Zootaxa, 2018)
The three larval instars of Huxelhydrus syntheticus Sharp, 1882, the only species of the New Zealand endemic genus Huxelhydrus Sharp, 1882, are described and illustrated including detailed morphometric and chaetotaxic analyses of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi. Larvae of this species are characterized by the absence of the primary pore ABc, shared with all other known Bidessini larvae and therefore representing a potential synapomorphy of the tribe. Third instars of Huxelhydrus can be separated from those of all other known Bidessini genera by the following combination of characters: larger size, mandibular pore MNa located in a clearly distal position with respect to pore MNb, and presence of secondary setae on dorsal surface of protarsus, on posteroventral surface of all tarsi, and on urogomphus. First instars, on their part, can be distinguished by the presence of: an occipital suture, the primary pore PAk, a ventroapical spinula on antennomere 3, and an anterotransverse carina on meso- and metathorax.